Addressing Disparities in Prenatal Care via Telehealth During COVID-19: Prenatal Satisfaction Survey in East Harlem - Futterman, Itamar; Rosenfeld, Emily; Toaff, Miriam; Boucher, Taryn; Golden-Espinal, Samantha; Evans, Kamilah; Clare, Camille A. (American Journal of Perinatology, 2020)
Objective In the setting of an inner city, safety net hospital, patient satisfaction with prenatal care conducted via telehealth was compared with in-person visits at the height of the novel coronavirus disease 2019 (COVID-19) pandemic.Study Design Through this cross-sectional study, patients were identified who received at least one televisit and one in-person visit during the COVID-19 pandemic. The Short Assessment of Patient Satisfaction (SAPS) survey was used to measure patient satisfaction. Surveys pertaining to in-person and televisits were conducted at the end of a telephone encounter, and overall satisfaction scores were documented. Patients were excluded if they received in-person or virtual care only and not both. The SAPS score correlated with the degree of patient satisfaction.Results A total of 140 patients were identified who received both virtual and in-person prenatal care from March 1, 2020 to May 1, 2020. One hundred and four patients (74%) agreed to be surveyed: 77 (74%) self-identified as Hispanic and 56 (54%) stated that their primary language was Spanish. The overall median satisfaction score for televisits and in-person visits was 20 (interquartile range [IQR]: 20, 25) and 24 (IQR: 22, 26) (p = 0.008, Z score = 2.651). In patients who self-identified as Hispanic or identified their primary language as Spanish, there was no statistically significant difference in their satisfaction scores.Conclusion While there were lower scores in patient satisfaction for televisits in every category, there were no clinically significant differences since all medians were in the “satisfied” range. By lowering patient exposure to severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), especially for those at risk for reduced access to care and higher COVID-19 cases by zip code, telehealth allowed for appropriate continuation of satisfactory prenatal care with no impact on patient perceived satisfaction of care.Key Points
Keywords: telemedicine; patient satisfaction; SAPS; COVID-19; prenatal care; Hispanic